(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The purpose of this study is to explore the factors that influence the integration of using artificial intelligence drawing tools into art and design education in colleges and universities. To integrate AI technology into art design education, it is first necessary to clarify the effect of the application of AI technology in the education process. Through the methods of literature review, case study, and practical teaching, we analyze the potential and influencing factors of the application of AI in education by integrating the theoretical foundations of art and design teaching with AI. This study summarizes the effects and possible shortcomings of the application of artificial intelligence from the case of universities in China and proposes corresponding countermeasures. The conclusions of the study can provide theoretical support and practical guidance for the application of artificial intelligence in art and design teaching.